Student’s perception towards learning medical sciences: problem based learning versus lecture based learning methods - TS., Padmanabha; G., Manu; Savkar, Madhav K.; T., Chandrakantha; K., Neha (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Problem-based learning (PBL) is one of the most commonly used educational methods in medical schools of different countries. By working through this method, students think critically, generate with ideas, and acquire the knowledge and skills required to become a doctor. The objectives were, this study aimed to compare problem-based learning with lecture-based learning in the education of medical students on different disciplines but addressing the 2nd year subjects as a whole & in particularly pharmacology. Methods: This cross-sectional observational study was conducted on medical students of Bidar Institute of Medical Sciences, Bidar. All the students were enrolled in the study were given with pretested questions after obtaining the institutional ethical clearance and informed consent from the students. Fully completed questionnaires were collected and analysed. Results: Students preferred problem-based learning over lecture-based learning (LBL) because of motivation boost, a higher quality of education, knowledge retention, class attractiveness, and practical use. However, the difference was not statistically significant. Although PBL edged over LBL, but most of them preferred integrated teaching going side by side, i. e, PBL along with LBL. Conclusions: Students’ percieves that the knowledge & understanding could be very easily acquired by PBL over LBL. Students felt Pharmacology should be taught with both ways, initially LBL followed by PBL for better understanding the concepts for clinical application.